Hubungan antara Kepuasan terhadap Sekolah dengan Subjective Well-Being Siswa SMP di Kota Bandung - Andi Arsita Soraya Mangkona; Ihsana Sabriani Borualogo (Bandung Conference Series: Psychology Science, 2022)
Abstract. School satisfaction among adolescents affects students school achievements greatly. A higer rate school satisfaction makes student achievements to be higher. Students spends a lot of time in school, so student welfare cannot be seen separately from the school context. The purpose of this study was to determine the correlation between satisfaction with school, level of students’ school satisfaction and their SWB, along with the factors of school satisfaction that most contribute to SWB in junior high school students of Bandung. This study uses quantitative research methods with a cross-sectional research design. The sampling technique used is stratified cluster random sampling. The measuring instrument used is a measuring instrument from Children's World, namely School Satisfaction, CW-SWBS5 and OLS. The participants of this study were 849 students with the percentage of students being 56.2% female students and 43.8% male students. The results of this study indicate that female students (M = 76.1) have higher school satisfaction than male students (M = 73.3%). Overall, junior high school students in Bandung have school statisfaction which is at a level slightly above the average (M = 75.13) and their SWB is at a level slightly above average (M = 79.91). The factor of satisfaction with school that contributes the most to overall life satisfaction is satisfaction with other students in class. And the most contributing factor to SWB is satisfaction with the things learned in school. Abstrak. Kepuasan terhadap sekolah di kalangan remaja sangat mempengaruhi prestasi belajar. Kepuasan terhadap sekolah yang tinggi membuat prestasi belajar siswa juga semakin tinggi. Siswa menghabiskan banyak waktu di sekolah maka kesejahteraan siswa tidak dapat dilihat secara terpisah dari konteks sekolah. Tujuan penelitian ini untuk mengetahui hubungan kepuasan terhadap sekolah, taraf kepuasan terhadap sekolah dan SWB siswa, beserta faktor-faktor kepuasan terhadap sekolah yang paling berkontribusi terhadap SWB pada siswa SMP di Kota Bandung. Penelitian ini menggunakan metode penelitian kuantitatif dengan desain penelitian cross-sectional. Teknik sampling yang digunakan yaitu stratisfied cluster random sampling. Alat ukur yang digunakan adalah alat ukur dari Children’s World yaitu School Satisfaction, CW-SWBS5 dan OLS. Partisipan penelitian ini berjumlah 849 siswa dengan persentase siswa yaitu 56.2% siswa perempuan dan 43.8% siswa laki- laki. Hasil penelitian ini menunjukkan siswa perempuan (M = 76.1) memiliki kepuasan terhadap sekolah yang lebih tinggi dibandingkan siswa laki-laki (M= 73.3%). Secara keseluruhan siswa SMP di Kota Bandung memiliki kepuasan terhadap sekolah yang berada pada taraf sedikit di atas rata-rata (M = 75.13) dan SWB siswa SMP berada pada taraf sedikit di atas rata-rata (M = 79.91). Faktor kepuasan terhadap sekolah yang paling berkontribusi terhadap kepuasan kehidupan siswa secara menyeluruh adalah kepuasan terhadap teman-teman lain di kelas. Dan faktor yang paling berkontribusi terhadap SWB siswa adalah kepuasan dengan hal- hal yang dipelajari di sekolah.